Dinuclear Chloride‐Binding Foldamers Based on Fluorescent Oligoureas. Issue 17 (3rd April 2013) - Yang, Peiju; Wang, Jiamin; Jia, Chuandong; Yang, Xiao‐Juan; Wu, Biao
Abstract: A series of dinuclear chloride‐binding foldamers – (TEA)2 [L 1 Cl2 ]· Et2 O (1 ), (TEA)2 [L 2 Cl2 ] (2 ), (TBA)2 [L 3 Cl2 ] (3 ), (TBA)2 [L 4 Cl2 ] (4 ), [K(18‐crown‐6)]2 [L 4 Cl2 ]· H2 O (5 ), and (TBA)2 [L 5 Cl2 ]· H2 O (6 ) – have been synthesized from naphthyl‐ and anthracenyl‐decorated oligoureas (tetrakisurea to hexakisurea, L 1 –L 5 ). In the crystal structures of1 –6, the oligoureas adopt helical conformations and two chloride anions are bound inside by the urea groups. The solution binding properties ofL 1 –L 5 toward chloride ion were investigated by 1 H NMR and fluorescence spectroscopy. Upon binding of the anions, characteristic downfield shifts of the NH signals and enhanced fluorescent emission relative to the free ligands were observed. In DMSO solution, the ligands each display a 1:1 binding ratio to chloride, with association constants of K = 1.16–7.58 × 10 2 M –1, which contrasts with the 1:2 (host to guest) binding mode in the crystal structures. However, the formation of dinuclear foldamers in the less polar solvent CHCl3 was indicated by the HRMS (ESI) spectra. Abstract : A series of dinuclear chloride‐binding foldamers have been synthesized from naphthyl‐ and anthracenyl‐decorated, ortho ‐phenylene‐bridged oligoureas (tetrakisurea to hexakisurea).